Perancangan Perbaikan Komunikasi Pemasaran Motiviga Menggunakan Metode Benchmarking dan Tool Analytical Hierarchy Process - Hanifah Prilia Sepnita Surosman; Husni Amani; Boby Hera Sagita (Peneliti.net, 2022)
Motiviga is a local fashion brand that was founded in 2012 in the city of Bandung and is an industry pioneer that produces bags made of scraf in Indonesia. Sales of Motiviga products from December 2020 to September 2021 fluctuated and tended to decline and did not meet the sales targets that had been set. One of the factors that caused the sales target not to be achieved, namely Motiviga is included in the low level of involvement. A low level of engagement means that followers on that account are less engaged in any content so the performance of uploaded content is low. As for other factors that can be a trigger in purchasing decisions, namely brand awareness of a product. Motiviga has implemented several marketing communication mixes in the use of its tools but it has not been carried out optimally. This can be a factor in not achieving sales targets and low brand awareness at Motiviga. This final project aims to design an integrated system for improving marketing communications using benchmarking and Analytical Hierarchy Process methods. A benchmarking method that will be used to get the best marketing communication design from Motiviga which can then be used as a reference in the proposed marketing communication program implemented by Motiviga in the hope of influencing brand awareness and increasing sales targets and also the Analytical Hierarchy Process tool that will be used to identify competitors selected as Motiviga's benchmark partner. The design of an integrated system for improving marketing communication programs at Motiviga has 15 attributes of needs from the results of data processing that has been carried out.